THE EFFECTIVENESS OF CONDUCTIVE EDUCATION ON MOTOR SKILLS IN CHILDREN WITH CEREBRAL PALSY (International Journal of Physiotherapy, 2017)
Background: Cerebral palsy is a nonprogressive neuro-developmental disorders that are caused by damage to the developing brain and affect movement and posture. Children with cerebral palsy suffer difficulty in motor function (coordination and control).The present inquiry investigated the impact of conductive education on motor skills in children having cerebral palsy.Methods: A quasi-experimental research was done using pretest-posttest and control group design. The study subjects consisted of all children with cerebral palsy in Shiraz. A sample of 30 subjects was randomly chosen to employ convenience sampling procedure and classified to two groups of treatment (15 subjects) and control (15 subjects). The pretest was performed for both groups, and the experimental group received conductive education in 20 sessions. While the control subjects did not have this education, finally, the post-test was performed for both groups. The Lincoln-Oseretsky test was used to measure motor skills. The data were analyzed using ANCOVA and MANCOVA.Results: The results showed that conductive education had a significant effect on motor skills (P